2015
DOI: 10.1002/app.42502
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy shape‐memory polymer reinforced by thermally reduced graphite oxide: Influence of processing techniques

Abstract: In this article, epoxy shape-memory polymer (ESMP) reinforced with 1 wt % thermally reduced graphite oxide (TrGO) was fabricated by solution blending and three-roll mill (TRM) mixing, respectively. Both blending techniques allowed a uniform TrGO dispersion in ESMP matrix, and the TRM mixing lead to an exfoliation of the TrGO worms. Compared with pristine ESMP, the TrGO/ESMP composites showed 36.4-41.1% increase in Young's modulus and 38.1-44.1% improvement in tensile strength. The TrGO/ESMP composite fabricate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
(48 reference statements)
1
15
0
Order By: Relevance
“…The fixed bending angle ( θ f ) was measured. Shape fixity ratio ( R f ) of the specimen can be calculated by: Rf=θnormalf180°×100% …”
Section: Methodsmentioning
confidence: 99%
“…The fixed bending angle ( θ f ) was measured. Shape fixity ratio ( R f ) of the specimen can be calculated by: Rf=θnormalf180°×100% …”
Section: Methodsmentioning
confidence: 99%
“…Carboxylic acid functionalized MWCNTs (MWCNT‐COOH, the COOH content: 3.86 wt %) and graphene nanoplatelets (GNPs) (thickness 4–20 nm, diameter 5–10 µm) were purchased from Chengdu Organic Chemistry Co. Ltd. of China. Functionalized graphene sheets (FGSs) were synthesized by exfoliating graphite oxide at 500 °C …”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the tensile strength of fluorinated MWCNT/epoxy composites increased by 31%, compared with the untreated MWCNT/epoxy composites. In a different study, it was found that, with the addition of 1.0 wt % graphene oxide to epoxy shape‐memory polymer, the tensile strength and Young's modulus were increased by 38.1–44.1% and 36.4–41.1%, respectively. Chatterjee et al .…”
Section: Introductionmentioning
confidence: 99%